Analisis Dampak Peralihan Jabatan Fungsional Umum Ke Jabatan Fungsional Tertentu - Master Supit Langi (Jurnal Ilmiah Wahana Pendidikan, 2021)
Increasing the effectiveness and efficiency of education performance in services is carried out on public works in certain functional jobs with the aim of creating fast, dynamic and professional employees. In its implementation, there are several habits that must be faced by ASN and organizations. The purpose of this research is to analyze the impact of functional positions to certain functional positions on the improvement of ASN performance after changing positions. The type of research used is descriptive qualitative with data collection techniques through interviews, documentation and observation. Informants who become resource persons are ASN who receive functional positions into certain functional positions. The results showed that the impact of the work of Manado State University employees in Tondano was not optimal, because socialization was still lacking, the increase in the rank of ASN was due to adjusting existing rules, and the need for debriefing/training in the framework of new functional positions. The conclusion from the simplification of work in the form of positions makes the burden on the State even greater because procurement and training for new positions are also not available for all patterns of career development for functional positions for types of positions. Suggestions that can be done are only functional activities paying attention to the professionalism of the previous ASN.